OBSTETRIC AND PERINATAL OUTCOMES IN PATIENTS WITH VERIFIED HIV STATUS - Abdullayeva, L.M.; Safarov, A.T.; Safarova, L.A.; Tugizova, D.I. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction: the priority areas of scientific research continue to be the determination of the medical and social characteristics of pregnant women with HIV, the study of the course of pregnancy, childbirth, postpartum and neonatal periods, the identification of risk factors and the development of modern methods for the prevention of perinatal complications in this patient population. Materials and methods of research: 119 HIV-infected pregnant women who applied to the AIDS Center of Tashkent and maternity complexes of Tashkent No. 1,8,9. general clinical, laboratory, immunological, special obstetric examination, instrumental, general morphological, morphometric, histochemical, morphometric and statistical research methods were used. Results: In the first half of gestation, 21% (10 women) of the 1st subgroup had a threatening spontaneous miscarriage, while 24% of the patients were hospitalized, 76% received outpatient treatment. In subgroups 2 and 3, the threat of termination of pregnancy was 10 (26%) and 7 (20.6%), respectively. The majority of women, 98 (82.3%), had a full-term pregnancy, 21 (17.6%) had premature birth. The diagnosis of a full-term healthy newborn occurred in 98 (82.4%). 30 newborns (22.2%) had perinatal lesions Conclusion: According to a retrospective analysis, pregnant women with HIV-positive status have a high rate of obstetric and neonatal complications